The Fasciola hepatica growth factor; FhTLM, and actions in immune evasion and parasite survival - Musah-Eroje, Mayowa (2020)
Helminth parasites promote the development of antigen-specific anergy and regulation which often limits pathology but allows parasite survival. Parasite effectors mediating this are the subject of intense study as they may be useful as future vaccine targets. Fasciola hepatica possesses a TGF-like molecule (FhTLM), part of a larger TGF family, which play an important role in regulating parasite development and modulating host immune responses. We hypothesized that F. hepatica may utilise FhTLM to down modulate host immune responses via induction of regulatory. Consequently, in this study, the immuno-modulatory properties of FhTLM with regards to its effect on T-cell mediated immunosuppression and modulation of host immune cells and signals to benefit parasite survival were studied.